Roller-Compacted Concrete for Road Use. Construction Aspects - Castro, Jorge Arturo (2025)
The equipment used for the construction of roller-compacted concrete (RCC) pavements is basically the same as that used for the mixing, transportation, placement, and compaction of asphalt concrete pavements. As is obvious, since it is a different material from the one for which the equipment was designed, certain considerations must be taken into account, which are detailed below.